Asymmetric error control for production systems in mechatronics - Vaideeswaran, J.; Muhammad Iqbal, Muhammad Hussain, Dr. (2012)
In the realm of E-manufacturing, the job tool movements should be precisely controlled which normally involve the directions East-West and South-North. Whereas the robot applications often involve either obstacle detection or target chasing as opposite tasks. Research shows that the application of electronics and advanced software will drive innovation to manufacturing process. Since the sensor based instrumentation will be utilized for the above tasks, the accuracy in tele-control required during data communication calls for bit-error detection and correction.